ANALYSIS OF BROILER CHICKEN FARMING BUSINESS IN GAMPONG BLANG DALAM, BANDAR DUA DISTRICT, PIDIE JAYA DISTRICT - Hamdani, Hamdani; Ibnu Yasier (PUCUK : Jurnal Ilmu Tanaman, 2024)
This research aims to analyze the broiler chicken farming business in Blang Dalam Village, Bandar Dua District, Pidie Jaya Regency, which has great potential in increasing farmers' income and meeting the increasing need for chicken meat. Broiler chicken farming in this area is promising due to the high market demand, both locally and more widely, as well as the relatively low costs of raising broiler chickens compared to other livestock. This research involved 110 broiler chicken breeders as a population, and 10 breeders were selected as samples using a purposive sampling method. Primary data was collected through direct interviews with breeders regarding personal characteristics and business profiles, while secondary data was obtained from various related agencies. The research results show that the average income of broiler chicken farmers in the research area reaches Rp. 38,938,444 per period with an R/C value of 1.48, which shows that this business is feasible and quite profitable. Apart from that, the broiler chicken marketing system in Gampong Blang Dalam is also considered efficient, which supports the sustainability of the broiler chicken farming business in the area. Thus, this business has bright prospects in improving the economic welfare of farmers and supporting the growth of the livestock sector in Bandar Dua District.